Postgraduate Paediatric Education in Indonesia - H.E. Monintja; W.T. Karjomanggolo; R. Sutejo (Indonesian Pediatric Society, 1979)
Previously the objectives of the postgraduate training program throughoutIndonesia were not clearly defined. The problems which served as objective determinants were also not defined. At present the Indonesian Paediatric Association, with her Board of Specialists, has succeded in laying down the fundamental of the curriculum of Indonesian Paediatrician. The government as well as the Indonesian Paediatric Association now realize that the postgraduate paediatric education system should be a